Faktor – Faktor yang Mempengaruhi Produksi Buncis di Desa Antapan, Kecamatan Baturiti, Kabupaten Tabanan - DANY NOVAN ARDIANSAH; I DEWA GEDE RAKA SARJANA; A.A.A. WULANDIRA SAWITRI DJELANTIK (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2019)
Factors that Influence the Production of Beans in Antapan Village, Baturiti Sub-District, Tabanan RegencyBean is a horticultural commodity that has potential and health benefits, and its consumption can increase because of the FAO recommendations and an increase inpopulation, but the production of beans is volatile. This condition causes no adequatenational bean consumption and reduces the bean farmers' income. The purpose of thestudy was to determine the factors that influence the bean production in the village ofAntapan. The research location was determined intentionally. The sampling methodused a census method for all bean farmers in Antapan Village, totalling of 30people.The research method uses the Cobb-Douglas production function. The researchfindings indicate that the F test results of six variables: seeds, labor, organic fertilizer,NPK fertilizer, fungicides, and insecticides affect simultaneously. Partially only organicfertilizer and NPK fertilizer had an effect (P <0,05) on the bean production.